EVALUASI KUALITAS LAYANAN WEB MENGGUNAKAN MODEL INTEGRASI FUZZY AHP-TOPSIS - Sutami, Sutami; W, Bambang Soedijono; Henderi, Henderi (Universitas Respati Yogyakarta, 2017)
AbstractThe study was made with the purpose of comparing the six Securities website service quality at the Galeri Investasi Yogyakarta. so give recommendations to web developers in building a website. As for the website is www.danareksa.com, www.valburysecurities.co.id, www.sucorinvest.com, www.phintracosecurities.com, www.firstasiacapital.com, and www.oso-securities.com. The measurement of the quality of service the website best of criteria Ease of use, Content, Accuracy, Timeliness of response, Privacy and determine the best Securities website of each criterion based on user presepsi service website in the Gallery of the investment. To get the best quality websites that use a combination of methods of Analitycal Hierarchy Process (AHP) Technique and method for Order Preference by Similitary to Ideal Solution (TOPSIS).The end result of this research shows from the five criteria, a securities website has the best quality of service is www.valburysecurities.co.id. For each criteria of service quality is the best website in the criteria of Ease of use, criteria www.valburysecurities.co.id Content www.valburysecurities.co.id, www.oso-securities.com, Accuracy criteria criteria Timeliness of response www.oso-securities.com, presepsi Privacy www.valburysecurities.co.id criteria based on user service website in the Galeri Investasi Yogyakarta.Keywords: Service quality, Fuzzy AHP, Fuzzy TOPSIS